Neurological signs and morphological cerebral changes in schizophrenia: An analysis of NSS subscales in patients with first episode psychosis - Heuser, Mark; Thomann, Philipp; Essig, Marco; Bachmann, Silke; Schröder, Johannes (Psychiatry research. Neuroimaging, 2011)
Neurological soft signs (NSS) comprise a broad range of minor motor and sensory deficits which are frequently found in schizophrenia. However, the cerebral changes underlying NSS are only partly understood. We therefore investigated the cerebral correlates of NSS by using magnetic resonance imaging (MRI) in 102 patients with first episode schizophrenia. NSS were assessed after remission of acute psychotic symptoms using the Heidelberg scale (HS), which consists of five NSS subscales (“motor coordination”, “complex motor tasks”, “orientation”, “integrative functions”, and “hard signs”). Correlations between NSS scores and cerebral changes were established by optimized voxel-based morphometry. NSS total scores were significantly associated with reduced gray matter densities in the precentral and postcentral gyri, the inferior parietal lobule and the inferior occipital gyrus. Both of the NSS subscales “motor coordination” and “complex motor tasks”, referred to motor strip changes but showed differential correlations with parietal, insular, cerebellar or frontal sites, respectively. The NSS subscales “orientation” and “integrative functions” were associated with left frontal, parietal, and occipital changes or bihemispheric frontal changes, respectively. The NSS subscale “hard signs” was associated with deficits in the right cerebellum and right parastriate cortex. Repeated analyses for white matter changes revealed similar results. These findings confirm the associations between NSS and cerebral changes in areas important for motor and sensory functioning. This variety of cerebral sites corresponds to the heterogeneity of NSS and are consistent with the hypothesis that NSS reflect both a rather generalized cerebral dysfunction and localized deficits specific for particular signs.
Gesehen am 21.09.2022